Answer:
-77
Step-by-step explanation:
Simply plug in: ![-(3-(-4))(3-(-4)(2))](https://tex.z-dn.net/?f=-%283-%28-4%29%29%283-%28-4%29%282%29%29)
Because the "-" sign is outside the parentheses, you would distribute.
It would then be: -3-4. *positive and negative=negative, negative and negative=positive. -3-4=-7. It would then be: (-7) · ((3-(-4)(2))
(-4)(2)=-8. →(3-(-8))=(3+8)=11. The equation would then be: (-7) · (11)= -77
Answer:
<em>37.3° </em>
Step-by-step explanation:
sin β =
⇒ β = arcsin
= <em>37.3°</em>
Answer: HEEEEEEYYYYYYYYYYYYYYYYYYYYYYYYYY!!!!!!!!!!!!!!!!!
Step-by-step explanation:
Answer:
502.4
Step-by-step explanation:
Use tangent because the side you know and the side with x are both legs.
Do 203/tan(22) and you should get your awnser.
You devide by 203 because the rule is opposite over ajacent and 203 is the opposite side.